CD248 induces PD-L1 expression on cancer-associated fibroblasts to promote NSCLC immune escape - Yang, Zeyang; Wang, Xuanyin; Zhu, Xu; Li, Long; Zeng, Xianling; Ren, Jiaming; Wang, Lu; Wu, Jiangwei; Zhang, Qiaoling; Wang, Siyu; Lu, Maoqin; Zhai, Juan; et al. (Frontiers in Cell and Developmental Biology, 2025)
BackgroundTumor immune escape is a critical step in tumor progression. Cancer-associated fibroblasts (CAFs) in the tumor microenvironment (TME) express abundant PD-L1 and suppress the functions of CD8+T cells, enablingd immune escape. CD248 is a candidate bioindicator for CAFs associated with non-small cell lung cancer (NSCLC), although its involvement in immune escape is not known.MethodsFibroblasts were isolated from tumor and normal lung tissues from patients. We detected the expression of CD248 and PD-L1 on CAFs. Then, the influence of CAFs inhibited the function of CD8+T cells promoting NSCLC immune escape was assessed in vivo and in vitro. Finally, explored the mechanisms of which CD248 induced PD-L1 expression on CAFs.ResultsHerein, we demonstrated that CD248 increased CAF PD-L1 levels, inhibiting CD8+T-cell function, thereby promoting NSCLC cell invasion and migration. CD248-induced FAK/Src/JNK/c-Jun axis activation promoted PD-L1 expression on CAFs. In tumor-bearing mice, lung tumors grew significantly slower, and the amount of granzyme B+CD8+T cells was greater in fibroblast-specific CD248 gene knockout mice than in wild-type mice. More importantly, we found that tislelizumab efficiency was improved in CD248 gene knockout mice.ConclusionOur findings demonstrate that CD248 activates FAK/Src/JNK/c-Jun, thereby inducing PD-L1 expression on CAFs, which promotes NSCLC immune escape.